2020
DOI: 10.21203/rs.3.rs-111024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NeoCLEAN: a multimodal strategy to enhance environmental cleaning in a resource-limited neonatal unit

Abstract: Background: Contamination of the hospital environment contributes to neonatal bacterial colonization and infection. Cleaning of hospital surfaces and equipment is seldom audited in resource-limited settings.Methods: A quasi-experimental study was conducted to assess the impact of a multimodal cleaning intervention (NeoCLEAN) for surfaces and equipment in a 30-bed neonatal ward. The intervention included cleaning audits with feedback, cleaning checklists, in-room cleaning wipes and training of staff and mothers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The most frequently cultured Gram-negative (GN) pathogens from neonatal BSI include Klebsiella pneumoniae, Escherichia coli, Enterobacter spp., Serratia marcescens, Acinetobacter baumannii and Pseudomonas aeruginosa (7)(8)(9). Factors contributing to neonatal colonization and/or infection with GN pathogens include poor compliance with hand hygiene, equipment and environmental cleaning recommendations, overcrowding, low nurse to patient ratios, overuse of broad spectrum antibiotics and delay in introducing breastmilk (10)(11)(12). A recent study in the neonatal wards at Tygerberg Hospital, South Africa showed that the highest aerobic colony counts were seen in moist surfaces, e.g., sinks, milk kitchen surfaces, humidifiers, and suction tubing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently cultured Gram-negative (GN) pathogens from neonatal BSI include Klebsiella pneumoniae, Escherichia coli, Enterobacter spp., Serratia marcescens, Acinetobacter baumannii and Pseudomonas aeruginosa (7)(8)(9). Factors contributing to neonatal colonization and/or infection with GN pathogens include poor compliance with hand hygiene, equipment and environmental cleaning recommendations, overcrowding, low nurse to patient ratios, overuse of broad spectrum antibiotics and delay in introducing breastmilk (10)(11)(12). A recent study in the neonatal wards at Tygerberg Hospital, South Africa showed that the highest aerobic colony counts were seen in moist surfaces, e.g., sinks, milk kitchen surfaces, humidifiers, and suction tubing.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the neonatal wards at Tygerberg Hospital, South Africa showed that the highest aerobic colony counts were seen in moist surfaces, e.g., sinks, milk kitchen surfaces, humidifiers, and suction tubing. The organisms cultured were mainly Enterococci, S. marcescens, K. pneumoniae, S. aureus and A. baumannii (11). Due to their prematurity and absence of a suckling reflex, preterm neonates are mainly fed via a feeding tube.…”
Section: Introductionmentioning
confidence: 99%